The challenges arising from the digital economy to the South African tax system and possible measures to address them (with a focus on corporate income tax for MNEs) - Datadin, Taruna (University of the Witwatersrand, Johannesburg, 2024)
The advances in technology and innovation in recent years have resulted in the growth of the digital economy. The digitalisation has changed the way businesses operate. This has resulted in challenges to the international tax system which was set up over a century ago and has compromised the South African corporate income tax base. This research report aims to understand the impact of the digital economy on South Africa’s corporate income tax system and to assess the proposed measures put forward to address the associated challenges. The proposed measures examined in this report are global solutions proposed as well as unilateral measures proposed or implemented by other countries to address the corporate income tax challenges arising from the digital economy. The proposed measures analysed in the report were limited to the OECD’s Two-Pillar Solution, Digital Service Tax and the Digital Permanent Establishment concept. A qualitative research method was used for this research paper. The analysis has been performed through a detailed literature review. Based on the analysis performed, a recommendation was reached in that South Africa should wait to implement the global solution (the OECD’s Two-Pillar solution) to address the challenges arising from the digital economy. It was also found that at this stage, the unilateral measures of the Digital Service Tax and the Digital Permanent Establishment concept are not recommended to be implemented in South Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce (specialising in Taxation) to the Faculty of Commerce, Law and Management, School of Accountancy University of the Witwatersrand, Johannesburg 2024
Keywords: Digital economy; UCTD; SDG-8: Decent work and economic growth